Kanye West's Adidas Era: Influence on Branding, Consumers, and Market Response - Sarjono, Haryadi; Raharja, Robertus Ronaldinho; Khayla Adzra Armelia; Sindhikara, Kathleen; Aulia , Rachel; silviya, ine (Manunggal Halim Jaya, 2025)
This study aims to investigate the business impact of the Kanye West controversy on Adidas, focusing on brand management, consumer perception, and market response. Using extensive research methods and data analysis, the study examines the multifaceted impact of West's actions on the Adidas brand ecosystem. The study explores how the interplay between West's public persona and Adidas' image management strategies affect consumer attitudes and purchasing behavior. The investigation reveals impacts across market segments and geographic regions while evaluating the effectiveness of Adidas' crisis management initiatives to mitigate negative impacts and maintain brand equity amidst turbulent times. The study also highlights the evolving nature of celebrity endorsements and their implications for modern-day brand partnerships. By combining theoretical frameworks with empirical evidence, the study contributes to a deeper understanding of the complex dynamics that shape brand-consumer relationships in the context of celebrity endorsements and corporate branding strategies. Ultimately, the study emphasizes the importance of proactive brand management and adaptive marketing strategies in navigating the dynamic contemporary brand management landscape.